2016
DOI: 10.1080/07359683.2016.1166854
|View full text |Cite
|
Sign up to set email alerts
|

Does trust of patients in their physician predict loyalty to the health care insurer? The Israeli case study

Abstract: This pioneer study tests the relationship between patients' trust in their physicians and patients' loyalty to their health care insurers. This is a cross-sectional study using a representative sample of patients from all health care insurers with identical health care plans. Regression analyses and Baron and Kenny's model were used to test the study model. Patient trust in the physician did not predict loyalty to the insurer. Loyalty to the physician did not mediate the relationship between trust in the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…With regards to service encounter, this study utilizes the “Service Encounter Assessment Model” Chang et al ( 21 ) and Gonzalez ( 2 ) to develop a study model and scale, and modified it to take into account the characteristics of the healthcare service industry. This study also references the nine patient trust measurement markers Gabay ( 36 ) and Castaldo et al ( 31 ) and the three trust measurement markers Huang et al ( 35 ). This study also integrates the trust and loyalty-related components valued by patients in the healthcare service industry with the markers developed by the aforementioned scholars.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…With regards to service encounter, this study utilizes the “Service Encounter Assessment Model” Chang et al ( 21 ) and Gonzalez ( 2 ) to develop a study model and scale, and modified it to take into account the characteristics of the healthcare service industry. This study also references the nine patient trust measurement markers Gabay ( 36 ) and Castaldo et al ( 31 ) and the three trust measurement markers Huang et al ( 35 ). This study also integrates the trust and loyalty-related components valued by patients in the healthcare service industry with the markers developed by the aforementioned scholars.…”
Section: Methodsmentioning
confidence: 89%
“…Regarding the relationship between patients' trust and loyalty ( 13 , 16 – 18 , 36 ), findings show that the degree of patients' trust positively influences loyalty, and ( 13 , 16 , 17 ) prior trust directly and positively affects consequent satisfaction. Alhatti ( 16 ) and Fatima et al ( 13 ) found that patients' trust under the perfect hospital service quality or service encounter can stimulate loyalty positively.…”
Section: Hypothesis Developmentmentioning
confidence: 97%
“…When patients perceive their doctors to be sincere, credible, honest and benevolent, trust will naturally exist in the relationship built (Berry et al, 2008). Previous studies such as Gabay (2016), Moreira and Silva (2015) and Zhou et al (2017) further attested that healthy and trustful relations between patients and doctors-especially in the private healthcare setting-can help retain existing patients. Hence, we further hypothesise that:…”
Section: Mohd-any Et Almentioning
confidence: 99%
“…Co‐production requires active collaboration between patients and doctors to create value and build patient loyalty. Hence, building patients' loyalty to their doctors ultimately functions as a profitable scheme for medical care service providers (Gabay, 2016). In the same vein, Meesala and Paul (2018) advocate that due to subsisting value co‐production mechanism in medical care services, patients build trust in physicians, which in turn create loyalty.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that a trustful relationship between physicians and other medical team members on one side and the patients and their families on the other side is really important to achieve the fundamental purposes in the "Art of Medicine" [1]. This is why in almost all of the "codes of medical ethics", this issue receives the highest level of attention.…”
Section: Dear Editormentioning
confidence: 99%